2017 development effectiveness review. (Development effectiveness review., 2018)
The annual per capita gross domestic product growth rate in developing member countries (DMCs) of the Asian Development Bank (ADB) remained robust at 5.4% in 2016 but declined slightly from the preceding year. Poverty reduction has continued, but 326 million of the regions people still lived below the extreme poverty line in 2013, according to the most recent data, and nearly 1 billion others were positioned only slightly above it. Inequality declined slightly in some ADB DMCs, but the gap between rich and poor remains substantial.While the success rates for ADBs sovereign policy based operations remained steady in 2017, the rate for sovereign projects dipped slightly after particularly strong 2016 results. The nonsovereign operations success rate fell as well. ADB continued its above target performance in delivering gender equality results, but it also faced an ongoing challenge to ensure that the outcomes and benefits of its projects are sustained. Most of the operations ADB completed in 2017 delivered their targeted results in ADBs core sectors of focus.